Molecular Dynamic Simulation of the Porcine Pancreatic Lipase in Non-aqueous Organic Solvents - Chen, Zi-Shi; Wu, Yi-Da; Hao, Jin-Heng; Liu, Yu-Jia; He, Kang-Ping; Jiang, Wen-Hao; Xiong, Mei-Jie; Lv, Yong-Si; Cao, Shi-Lin; Zhu, Jie (Frontiers in Bioengineering and Biotechnology, 2020)
In this paper, the conformational stability of Pocine Pancreas Lipase (PPL) in the three non-aqueous organic solvent, including DMSO, PRG and EtOH, was investigated by using molecular dynamic simulation. The root mean square deviations (RMSD), radius of gyration (Rg), solution accessible surface area (SASA), radial distribution function (RDF), hydrogen bond (H-bond), Ramachandran plot analysis, secondary structure, and the enzyme substrate affinity of the PPL in the organic solvent were comparably investigated. The results showed that the backbone and active pocket RMSD, hydrophilic ASA of PPL in three solvents increase with the increasing of the solvent LogP, while the Rg, hydrophobic ASA, hydrogen bond between solvent and PPL decrease. Among the three organic solvents, DMSO acts as a better solution, in which the PPL can be loose and extended and retained its native backbone in DMSO better than in PRG and EtOH. Moreover, Ramachandran Plot Analysis indicated that the PPL structure quality in DMSO was higher than that in PRG and EtOH. Also, the molecular docking results showed that PPL in DMSO exhibited the highest enzyme-substrate affinity comparing with PRG and EtOH. Generally, this study gives a molecular insight of the PPL structure in the non-aqueous organic solvents.